Extraction of eugenol from betel leaves (Piper betle L.) using hydrodistillation and supercritical carbon dioxide technique - Nik Hadzir, Noor Hadzuin (2012)
Betel (Piper betle L.) is one of the precious herb plants originated from Malaysia. The leaves of betel have been used traditionally for various medicinal purposes. Scientific research on the leaf of this plant claims that it possesses many beneficial bioactivities. Extract from betel leaves has a great potential to be used in developing commercial products. However, there is lack of research on the processing aspects to produce its bioactive extract. Many extraction methods are widely used in extracting bioactive compounds. However, each method is different since it has advantages and disadvantages. This study focuses on two processes involved in producing bioactive extract of betel leaves namely hydrodistillation and supercritical fluid extraction. Different experiments were designed and carried out to look into the effects of various operating parameters. The first part of this study investigated the effect of type of leaves and extraction time on yield and composition of eugenol by using conventional hydrodistillation method. Results of the study showed that fresh betel leaves were more preferable over dried betel leaves. Six hours was compatible for extraction of fresh betel leaves. The second part of this study is to examine effect of pressure and temperature on yield and concentration of eugenol by using supercritical fluid extraction. Response surface methodology (RSM) was applied to obtain the optimum process parameter. Optimized pressure and temperature which were suggested by RSM are 190 bar and temperature 50 °C. The predicted properties of extract are 0.5% yield and 21.57 mg/ml concentration of eugenol. The kinetic model was used to describe the mass transfer phenomena. The highest value of mass transfer coefficient was found to be 0.208 min-1 at pressure 160 bar and temperature 50 °C. Del Valle-Aguilera model showed the best fit with experimental data with lowest average absolute relative deviation (AARD). This equation is recommended for betel oil solubility in supercritical fluid extraction.Comparison of supercritical carbon dioxide technique and hydrodistillation was studied. Supercritical carbon dioxide technique offers many important advantages over hydrodistillation. Therefore, this technique can be considered as a distinguished technology for the extraction of betel leaves,not only due to proclaimed advantages over the conventional techniques but also due to the high target compound concentration and yield with short extraction time (1 hour).